Review of Thermal Calculation Methods for Boilers—Perspectives on Thermal Optimization for Improving Ecological Parameters - Bartosz Ciupek; Andrzej Frąckowiak (Energies)
This article presents an overview of thermal calculation methods used in boilers powered by fossil fuels (solid, liquid or gas). The analysis was carried out mainly in terms of combustion chamber calculation methods. Changing standards and legal regulations regarding the use of fossil fuels in Europe and the world make it necessary to adapt calculation methods and boiler design to current requirements, and many of them are related to outdated boiler models or for fuels that are no longer so heavily used in industrial solutions. Current research and development trends implemented in the EU and in the world related to the issues of the European Green Deal, the Fit for 55 directive and other ecological trends in the energy sector make it necessary to verify and remodel the calculation methods used so far in terms of the thermal efficiency of the device, fuel consumption or the use of fuels not previously used in their wide range in a wider application. Hence, the knowledge and updating of the state of knowledge in the field of the thermal calculation of boilers in terms of their environmental performance is necessary and strongly sought after by researchers. It is undoubted that in the next few years, boilers will continue to be the main source of thermal energy, especially in the power industry or industry. A reasonable energy transition should be based on the direction of the thermal optimization of already functioning structures and adaptation of their operating parameters to the planned new ecological fuels in the sense of the intensification of energy converted from primary form to thermal energy, and in the last step, it should reorganize the energy and industrial sectors, leaving only these groups of devices treated as a stable and necessary source of energy. Therefore, it should be recognized that activities aimed at improving the thermal parameters of boilers should directly improve the thermal efficiency of the device, and this will translate into fuel savings and reduce their negative impact on the environment.